Warranty of occupational health and safety within public health insurance in public opinion in Poland - Bojar, Iwona; Szymańska, Jolanta (Polish Journal of Public Health, 2010)
Introduction. Public health care systems are aimed at the enhancement of health of the population and decrease in health inequalities.Aim. The aim of the study was the analysis of social opinion concerning health safety of the Polish population within the system of public health insurance (PHI) in Poland.Material and methods. The study was conducted anonymously among various social groups in Poland in 2008. The research tool was a questionnaire form designed by the authors for the needs of the presented study. The instructions were mailed, and 711 correctly completed questionnaires were returned. The results were subject to statistical analysis.Results. The respondents evaluated the opportunities of treatment in public health care – the same for all the insured – to be 2.21 according to a five-degree scale. Males perceive the possibility of equal access to health care within the PHI differently to females and respondents with various levels of education. The greatest problem associated with the use of public health care is a long waiting time after the registration for a specialist visit (87%), and for the performance of diagnostic tests (56.54%). Nearly 60% of the respondents expressed an opinion that there is no warranty of health safety within the PHI in Poland. Public health care services partially meet the expectations of 50% of the respondents, while 31.5% admit that their expectations are not satisfied.Conclusion. The majority of respondents indicated that both the State, creating an efficient system of health protection, and the citizens themselves are responsible for the state of the Polish health care system